Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

What would be the derivate of square roots? For example if i have $2 \sqrt{x}$ or $\sqrt{x}$

Im unsure how to derive these and include them especially in something like implicit

share|cite|improve this question
up vote 10 down vote accepted

$\sqrt x=x^{1/2}$, so you just use the power rule: the derivative is $\frac12x^{-1/2}$.

share|cite|improve this answer
what about something like $2\sqrt{x}$ – soniccool Jun 29 '12 at 21:51
@soniccool: The derivative of $2f(x)$ is always twice the derivative of $f(x)$. So the derivative of $2\sqrt x$ is $2\cdot\frac12x^{-1/2}$. – MJD Jun 29 '12 at 21:52
@soniccool: You mean $\left(2\sqrt x\right)'=\frac1{\sqrt x}$. For the same reason that the derivative of $2x^3$ is $6x^2$: the derivative of $af(x)$ is $af'(x)$. In this case you have the derivative of $2x^{1/2}$, which is $$2\left(x^{1/2}\right)'=2\cdot\frac12x^{-1/2}=x^{-1/2}=\frac1{\sqrt x}\;.$$ – Brian M. Scott Jun 29 '12 at 22:19
Yes. Let $$y = 4\sqrt{x}$$ $$y' = 4(\frac{d}{dx} \sqrt{x})$$ $$y' = 4\cdot \frac{1}{2\sqrt{x}}$$ $$y' = \frac{2}{\sqrt{x}} $$ – Joe Jun 29 '12 at 22:49
@soniccool: You’re welcome. – Brian M. Scott Jun 29 '12 at 23:04

Let $f(x) = \sqrt{x}$, then $$f'(x) = \lim_{h \to 0} \dfrac{\sqrt{x+h} - \sqrt{x}}{h} = \lim_{h \to 0} \dfrac{\sqrt{x+h} - \sqrt{x}}{h} \times \dfrac{\sqrt{x+h} + \sqrt{x}}{\sqrt{x+h} + \sqrt{x}} = \lim_{x \to 0} \dfrac{x+h-x}{h (\sqrt{x+h} + \sqrt{x})}\\ = \lim_{h \to 0} \dfrac{h}{h (\sqrt{x+h} + \sqrt{x})} = \lim_{h \to 0} \dfrac1{(\sqrt{x+h} + \sqrt{x})} = \dfrac1{2\sqrt{x}}$$ In general, you can use the fact that if $f(x) = x^{t}$, then $f'(x) = tx^{t-1}$.

Taking $t=1/2$, gives us that $f'(x) = \dfrac12 x^{-1/2}$, which is the same as we obtained above.

Also, recall that $\dfrac{d (c f(x))}{dx} = c \dfrac{df(x)}{dx}$. Hence, you can pull out the constant and then differentiate it.

share|cite|improve this answer
This is both exceedingly complete, and utterly useless for the OP. Good work! (+1) – Chris Taylor Jun 29 '12 at 22:01
This is the best answer here, because it doesn't assume that the power rule (which is easy to prove when the exponent is a positive integer) automatically applies when the exponent is NOT a positive integer. – user22805 Jun 29 '12 at 22:47

Let $f(x) = \sqrt{x} = x^{1/2}$.

$$f'(x) = \frac{1}{2} x ^{-1/2}$$

$$f'(x) = \frac{1}{2x^{1/2}} = \frac{1}{2\sqrt{x}}$$

If you post the specific implicit differentiation problem, it may help. The general guideline of writing the square root as a fractional power and then using the power and chain rule appropriately should be fine however. Also, remember that you can simply pull out a constant when dealing with derivatives - see below.

If $g(x) = 2\sqrt{x} = 2x^{1/2}$. Then,

$$g'(x) = 2\cdot\frac{1}{2}x^{-1/2}$$

$$g'(x) = \frac{1}{x^{1/2}} = \frac{1}{\sqrt{x}}$$

share|cite|improve this answer

The Power Rule says that $\frac{\mathrm{d}}{\mathrm{d}x}x^\alpha=\alpha x^{\alpha-1}$. Applying this to $\sqrt{x}=x^{\frac12}$ gives $$ \begin{align} \frac{\mathrm{d}}{\mathrm{d}x}\sqrt{x} &=\frac{\mathrm{d}}{\mathrm{d}x}x^{\frac12}\\ &=\frac12x^{-\frac12}\\ &=\frac{1}{2\sqrt{x}}\tag{1} \end{align} $$ However, if you are uncomfortable applying the Power Rule to a fractional power, consider applying implicit differentiation to $$ \begin{align} y&=\sqrt{x}\\ y^2&=x\\ 2y\frac{\mathrm{d}y}{\mathrm{d}x}&=1\\ \frac{\mathrm{d}y}{\mathrm{d}x}&=\frac{1}{2y}\\ &=\frac{1}{2\sqrt{x}}\tag{2} \end{align} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.